The Influence of Severity Violation, Demographic Factors and Organizational Factors on Whistleblowing Intention - Chandra Alamsyah; Dwi Putra Ismawan (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2019)
One of the factors that motivate someone to become a whistleblower is demographic factors such as gender and ethnicity. Another factor that can motivate someone's intention to do whistleblowing is managerial status. High-level managers, have positive perceptions about whistleblowing and may do whistleblowing, so the authors are interested in examining the influence of the seriousness of violations, demographic factors and organizational factors on whistleblowing intentions. The sample in this study is the financial section of the Central Java Regional OJK Work Unit. The number of samples in this study were 86 respondents because they felt they could represent the total number of accountants. Based on the discussion in this study, the researcher concludes that several results of the study stated that the saverity of the violation had a significant positive effect on whisteblowing intention, That is, if the level of severity is more serious, then one's intention to do whistleblowing will increase.